'White flour, white sugar, white rice, white salt': Barriers to achieving food and nutrition security in Kiribati. (May 2021) - Cauchi, John Paul; Bambrick, Hilary; Correa-Velez, Ignacio; Moncada, Stefano
Highlights: Limited food choices in the Pacific contribute to poor health outcomes. Poor governance is a determinant of failed food security projects. Rice and sugar dominate food supplies in remote atoll countries such as Kiribati. Local food processing facilities may boost domestic market and improve food security. Low-tech options that limit reliance on outside aid can boost food security. Abstract: Food security is identified as one of the main challenges for the 21st century. In the Pacific islands this is especially the case due to natural, topographical, social, environmental, and economic constraints and the influence of globalisation that has forced many populations to resort to imported food. While hunger is rarely experienced by households, poor nutrition leads to a considerable noncommunicable disease burden. The effects of climate change will further exacerbate food security challenges in the region. Kiribati has one of the highest prevalence rates for obesity, diabetes and hypertension anywhere in the world. While past studies have explored regional and state-level food security challenges, there is comparatively little literature on household-level decision making processes related to food. Through focus group discussions and semi-structured interviews, we identified several themes describing challenges to achieving food security in the island nation, including several environmental challenges that hinder food security. We also include some policy recommendations based on these findings. These challenges and policy recommendations may be applicable to other atoll island communities in the Pacific and other remote coastal communities worldwide.